#TITLE_ALTERNATIVE# - PUJI RAHARDJO (NIM 13702036), ALEXANDER
Refractory materials have an important role in many high temperature processing industries. One of the revolutionary categories of refractories is castables, which refractories are made and heated in-situ. To improve its mechanical properties, castable refractory can be reinforced with short steel fibers that distributed in the refractory matrix (Steel Fiber Reinforced Castable Refractory method). But, this method can give differences in mechanical properties of refractory due to fibers that did not always be distributed evenly. The research was carried out to study the influence of equally distance woven steel fiber volume fraction, and the influence of firing temperature to cold compressive strength (CCS) property of LAMJ-1 commercial refractory (alumina spinel castable). Woven steel fiber were expected to give homogeneity of mechanical properties, while variation of firing temperature was done to see the ability of refractory to withstand compressive stress before its optimum strength (sintered). The research was done with cold compressive test of samples with five variations of firing temperature and three variations of steel fiber reinforce volume fraction. Phase compositional and micro structural characterizations were done by using XRD and SEM/EDS. The compressive strength of each firing temperatures depend on the transformation of LAMJ-1 minerals. The compressive strength for 0% fiber at 105 degrees C, 350 degrees C, 816 degrees C, 1150 degrees C and 1400 degrees C are 21.77 MPa, 25.18 MPa, 20.08 MPa, 28.71 MPa and 44.57 MPa. Adding fiber volume fraction at 105 degrees C to 816 degrees C can increase the compressive strength of LAMJ-1. For 0.82% fiber, the compressive strength at 105 degrees C, 350 degrees C, and 816 degrees C are 44.19 MPa, 49.45 MPa, and 35.4 MPa. While, for 1.64% fibers, the compressive strength at 105 degrees C, 350 degrees C, and 816 degrees C are 65.91 MPa, 71.22 MPa, and 40.52 MPa. At 1150 degrees C, the steel fiber reinforce cannot increase the compressive strength due to oxidation. The compressive strength for sample with 0.82% fibers and 1.64% fibers are 32.07 MPa and 29.76 MPa. From the standard deviation obtained, the use of woven fiber shows homogeneity in cold compressive strength. Further study should be carried out to have a more understanding on the mechanism of CCS decreasing between 350 degrees C-816 degrees C. The use of high temperature corrosion resistance woven fiber should be observed further and the effects on CCS increase.